Ceny na rynku nieruchomości a kredytowanie hipoteczne - Półtorak, Bogusław (Impact of Real Estate Prices on Mortgage Financing, 2006)
The level of real estate prices is connected with possibilities of real estate market financing and external financing share in the global amount of real estate. Cheap mortgages cause the increasing of real estate prices in the period of prosperity. It leads to the growing mortgage demand. In this case commercial banks have to estimate the value of collateral more carefully. It is necessary for them to manage safely in the long-term.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 238-249